Development and validation of highly sensitive multiplex real-time RT-PCR assay for detection of classical swine fever virus genome - A. S. Sadchikova; A. S. Igolkin; R. S. Chernyshev; A. A. Kozlov; I. S. Kolbin; A. V. Sprygin; D. A. Biryuchenkov; I. A. Chvala; A. Mazloum (Ветеринария сегодня)
Classical swine fever (CSF) remains a challenge for pig farming industrial lover the world despite the measures taken. The last CS  case in the Russian Federation was reported in 2020, however, the threat of the disease emerging still persists. A set of anti-epidemic measures including mainly preventive vaccination and annual diagnostic monitoring using molecular-genetic and serological methods is required for CSF virus introduction prevention and rapid eradication of potential disease out breaks. Therefore, areal-time reverse transcription-polymerase chain reaction using an internal control sample has been developed. Therefore, areal time reverse transcription-polymerase chain reaction using an internal control sample has been developed. Modified primers (locked nucleic acids containing conformationally blocked nucleosides) providing a higher affinity to the DNA matrix and physico-chemical stability and a FAM-labeled TaqMan probe were selected for 5’-untranslatedregion of the genome. The following validation parameters were defined: accuracy, repeatability, reproducibility, specificity and sensitivity. For comparative analysis of the developed as say sensitivity, swabs, samples of organs and tissues collected from pigs experimentally infected with an epizootic strain of the classical swine fever virus (spleen, kidney, liver, blood, lymph nodes, rectal and oral smears), animal-contaminated feed and virus-containing material with known virus titres were also tested in parallel with coded test systems No. x1 andx2. The developed assay was shown to have 100% diagnostic sensitivity and detection limit of 0,23 lgCCID50/cm3. Therewith, there sults of analysis of test systems No. x1, x2 based on above parameters were lower that could give rise to false positive real-time RT-PCR results and incorrect diagnosis. Thus, described assay can be used for extensive monitoring of classical swine fever in the Russian Federation